1998
DOI: 10.1042/bj3301201
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale production and purification of the human green cone pigment: characterization of late photo-intermediates

Abstract: We present the first characterization of the late photo-intermediates (Meta I, Meta II and Meta III) of a vertebrate cone pigment in a lipid environment. Marked differences from the same pathway in the rod pigment were observed. The histidine-tagged human green cone pigment was functionally expressed in large-scale suspension cultures in Sf9 insect cells using recombinant baculovirus. The recombinant pigment was extensively purified in a single step by immobilized metal affinity chromatography and displays the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…Spalax is very similar to the human rod pigment in this respect (19). Note that the decay of meta II is typically much faster in cone pigments (t1 ⁄2 Ͻ 3 min (20)). The structural transitions accompanying receptor activation were probed by fourier transform-infared difference spectroscopy and were found to be almost identical to recombinant His-tagged bovine rhodopsin (not shown).…”
Section: Structural and Functional Characterization Of The Spalaxmentioning
confidence: 68%
See 1 more Smart Citation
“…Spalax is very similar to the human rod pigment in this respect (19). Note that the decay of meta II is typically much faster in cone pigments (t1 ⁄2 Ͻ 3 min (20)). The structural transitions accompanying receptor activation were probed by fourier transform-infared difference spectroscopy and were found to be almost identical to recombinant His-tagged bovine rhodopsin (not shown).…”
Section: Structural and Functional Characterization Of The Spalaxmentioning
confidence: 68%
“…Preparation of bovine retina lipids and removal of the detergent through addition of ␤-cyclodextrin to a final concentration of 20 mM were performed as described before (11). Purification of the proteoliposomes containing the reconstituted pigment was accomplished on a discontinuous sucrose gradient (10,20, and 45% sucrose (w/w)) in buffer F (11). After 16 h of centrifugation at 120,000 ϫ g and 4°C the pigment containing proteoliposomes were isolated from the 20 -45% interface and diluted with 4 volumes of buffer B.…”
Section: Methodsmentioning
confidence: 99%
“…As we reported earlier (DeGrip et al, 1999), the optimal solubilization conditions used during extraction of visual pigments are receptor-speciWc. Chaps provided the highest extraction eYciency for HGH (>80%) with DDM being signiWcantly less eYcient (50-70%) (Vissers et al, 1998). Thermal stability tests using various detergents showed that the longest half-life for the wt green cone pigment was observed in 10 mM Chaps in buVer B (70 § 30 h at 4°C), with 10 mM DDM as second best (40 § 20 h at 4°C).…”
Section: Hgh Mutantmentioning
confidence: 98%
“…However, Chapssolubilized HGH showed very poor binding to a variety of matrices available for immobilized metal aYnity chromatography (IMAC). The presence of DDM appeared to be imperative to allow IMAC-based puriWcation (Vissers et al, 1998). A compromise was found in a mixture of 10 mM Chaps and 10 mM DDM, that aVorded reasonable stability (half-life of 50 § 20 h at 4°C) and permitted IMAC-based puriWcation provided low Xow rates were applied during binding to and elution from the matrix (Bosman et al, 2003).…”
Section: Hgh Mutantmentioning
confidence: 99%
See 1 more Smart Citation